Peranan Iklan Dan Promosi Penjualan Produk Jasa Perbankan Terhadap Loyalitas Nasabah Pada PT Bank International Indonesia Cabang Bogor - Hayati, Titi (Jurnal Ilmiah Ranggagading (JIR), 2003)
Competition in banking has triggered PT Bank International Indonesia in promote new product to society. To make prospective client or customers interested , it was been conducted numerous of ways such as promotion by means of advertisements in various mass media ( television, newspaper, or magazine), exhibition, spreading brochures, etcetera. In the uncertainty of PT Bank International Indonesiaâs destiny, which is now under BPPNâs care, effort to maintain the costumers keep have loyalty are required. That is why, how far Advertisements and marketing promotion have gone for the sake of their loyalty to BII must be considered